Gain investigation for commercial GaAs and SiGe HBT LNA's under electron irradiation - Youssouf, Abdouraouf S.; Habaebi, Mohamed Hadi; Ibrahim, S.Noorjannah; Hasbullah, Nurul Fadzlin (IEEE, 2017)
In this paper, a characterization and comparison between the effects of Electron irradiation on low noise amplifiers (LNAs) implemented in a Silicon-Germanium (SiGe) Heterojunction Bipolar Transistor (HBT) and Gallium-Arsenide (GaAs) HBT technologies, respectively, was carried out. Previous studies [1] have shown that the properties of SiGe and GaAs HBT's are very tolerant to gamma, neutron, and proton irradiation without additional radiation hardening. Nowadays, commercial on the shelves (COTS) LNAs have been used in CubeSat communication system lunched in Low and Medium Earth Orbits. It therefore believed that the electron radiation in space may degrade the LNA's performance and lead to its failure. This is shows the importance of such investigation in evaluating and comparing the performance of the GaAs and SiGe LNAs which represent an important module in the front end of the communication receiver system. Two samples of GaAs and SiGe have been selected: the ADL 5523 GaAs and the SiGe BFU730F LNAs which are respectively cover a frequency range of 400MHz to 4 GHz and 2.3 to 2.7 GHz. Samples were irradiated with 3 MeV Electron doses ranging from 50 kGy to 250 kGy in the Electron Beam Irradiation Centre (Alutron), Nuclear Malaysia Agency. Results measurement have been carry out in the RF Laboratory in the faculty of engineering (IIUM), using the vector network analyzer 50 GHz. The results indicate that both SiGe and GaAs HBT technologies have been affected by the electron Irradiation.